Self-Acceptance Ibu Yang Memiliki Anak Autis Di Pusat Layanan Autis Naimata Kupang - Barimbing, Maryati Agustina; Feoh, Fepyani Thresna; Huke, Bendina Yunita (NHM PRESS, 2023)
Every parent hopes for a physically and mentally healthy child. However there are some baby are born and grow up with physical or mental disorder, like as autistic children. This condition makes mother feel sad, embarrassed and not ready to accept her child’s conditions. Self-acceptance is needed by mothers so that mothers love and accept themselves in facing difficulties while caring for children. This research aims to determine the description of self-acceptance of mothers who have autistic children at the Naimata Kupang Autism Treatment Center. This research was quantitative research using a descriptive research design. The sample in this study consisted of 32 poople who were selected by total sampling tecniques. This research instrument uses a self-acceptance questionnaire. it was found that the majority (96.9%) of mothers who had autistic children at the Naimata Kupang Autism Treatment Center were in the high Self-acceptance category. Mothers who have autistic children at the Naimata Kupang Autism Treatment Center have to maintain their self-acceptance by always being grateful for they grateful for they child is a gift from God, having an autistic child does not become an obstacle for the mother carry out activities so that mothers remain optimistic in caring for their children.